Tadābīr al-dawlah al-‘Uthmānīyah li ḥalli al-qaḍāyā al-mu’aqqadah li ḥujjāj al-Jāwī 1849–1916: Dirāsat fī ḍaw’i wathā’iq al-Arshīf al-Uthmānī - Ahmed, Asmahan Mostafa Tawfik Khalil (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
This article examines the challenges faced by hajj pilgrims from the Malay world and the efforts of the Ottoman Empire to accommodate them amidst the intervention of Dutch and British colonial powers in the 19th century. Utilizing documents sourced from the Ottoman Archives of the Presidency of the Republic of Turkey in Istanbul from 1849 to 1916 CE and employing historical research methods, this study delves into the economic dimensions of the Hajj during the late colonial period in Indonesia and the declining years of the Ottoman Empire. The article reveals the socio-economic difficulties experienced by Muslims from the Malay world in performing the Hajj due to exploitation by colonial powers and local government elites in the Hijaz region at that time. Although the documents indicate efforts by the Ottoman government to ensure the comfort of the pilgrims and prevent abuse of authority by local and colonial governments, it did not fully resolve the chaos in the Hajj implementation system at that time. These situations caused by Ottoman limitations in the global political arena and inflamed by their involvement in World War I.